Shaping the Future: Insights from a Longitudinal Study on Women’s Career Aspirations during Pregnancy and Postpartum - Ražauskienė, Vilma (Socialinė teorija, empirija, politika ir praktika, 2024)
This longitudinal study delves into the meanings of work for women during a transitional life stage. While the topics of opting out and opting in have garnered considerable attention, certain aspects of career development after childbirth remain underexplored. Existing literature often dichotomizes women into two primary groups, and some theories propose a three-group classification. However, such divisions may be overly simplistic and not universally applicable to all women. The objective of this study is to enhance the understanding of women’s career aspirations. In order to achieve this objective, two waves of individual semi-structured interviews with ten women at two specific time points were conducted: during pregnancy and four to six months postpartum. The results of the study demonstrate that the meaning of work for the research participants varied both during pregnancy and after childbirth. Additionally, some participants had alteredtheir career aspirations after they became mothers. The salience of the new identity as a mother is discussed as a possible precursor explaining adjustments in the career aspirations. This research enriches the discourse on work–life balance preferences by offering valuable insights into how early motherhood shapes women’s career goals, decisions, and expectations.